The contribution of endo-1, 4-β-D-glucanases to cellulolysis in Trichoderma koningii - Halliwell, G.; Abdul Wahab, Mohd. Noor; Patel, A. H. (Academic Press, 1985)
Cellulolytic culture filtrates of Trichoderma koningii have been extensively purified solely by molecular-sieve and anion-exchange chromatography under selected conditions. Seven components were isolated, principally endoglucanases but also two (including one minor) cellobiohydrolases. Five of these components, each with little of the other cellulolytic activities, together comprise the cellulase complex of the culture filtrate. In addition to the three more readily recognized components of the complex (β-glucosidase, an endoglucanase/CM-cellulase, and cellobiohydrolase), two additional components (endoglucanases) have been found to contribute to cellulolysis. Acting alone on cotton or reactive cellulose, each of the five enzymes had only weak saccharifying power. The three endoglucanases showed little interaction themselves on cellulose but synergized to different extents with the cellobiohydrolase on reactive cellulose and on cotton. Significant contributions to cellulolysis were also evident in ternary (and quaternary) mixtures involving either (or both, respectively) of the two new endoglucanases and cellobiohydrolase plus the third endoglucanase. Of particular interest was the combined action of the two new endoglucanases in cooperating with cellobiohydrolase (both on cotton and on reactive cellulose) in replacing to considerable extent what is usually considered the main and only essential endoglucanase.